ANALISIS TINGKAT KEUNTUNGAN USAHATANI BAWANG DAUN (Allium fistulusom L) DI DESA SINGA GEWEH KECAMATAN SANGATTA SELATAN - Nila Kusumawati; Istikomah Istikomah; Shinta Nabela Insani (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
The aims of this research were to know the shallot farming income and profit level. The research was conducted in the Singa Geweh Village including Sangatta Selatan District from May until July 2022. Data was collected using a survey method assisted by questionnaires as a data collection tool. Total population as well as a sample of 10 people taking a total sampling. The data analysis by calculating income (I) and R/C ratio. The results of that study obtained a total production cost of Rp.12.995.116 once time the leek planting period. Total revenue of Rp. 29.700.000 and income of Rp. 16.704.884. The profit level of the R/C ratio is 2,3. These results indicate that shallot farming in the Singa Geweh Village is profitable.